Motives of Female Crime in Kurdistan Society: A Field Study in the Department of Women’s Correctional Facility in Erbil - Hassan, Shnow Xalil (Journal of Tikrit University for Humanities, 2023)
Despite the low percentage of women’s crimes compared to crimes committed by men according to the mentioned statistics, it is noticeable that they have begun to take an upward trend in recent years, as these statistics represent figures announced only by officials which keep many of these crimes in a state of secrecy, especially in traditional societies such as the Kurdish society. This fact, if anything, confirms the seriousness of this phenomenon because it concerns an important and effective segment of society. Therefore, the current study entitled "The motives of female crime in Kurdish society" came because women’s crimes have appeared in reality and have become a tangible phenomenon in Kurdish society as well as crime in men, which calls for study and research on their motives and patterns. The problem of the study centered on the motives of female crime in the Kurdish society and to answer this, the researcher adopted the descriptive approach to suit the purposes of the study. Similarly, several questions were formulated, including: 1- What are the causes and motives of crime among women in Kurdish society? 2- Are there statistically significant differences between the causes and motives of the crime according to some of the personality traits of women in Kurdish society who commit the crime? The approach which is used in this study is the method of social survey (by the method of the comprehensive survey) in the sense of taking all the vocabulary of the research community, represented by all the inmates sentenced in the Department of Women’s Correctional Facility in Erbil during the year (2021), which number (86) women and one of the means of collecting data is the questionnaire, and regarding the results of the study and based on the results of calculating the arithmetic averages of the motives of female crime in Kurdistan Kurdish society. Economic factors came in the first place. They obtained the highest arithmetic average compared to the rest of the motivations which was (4.29) and with a standard deviation (0.59) which is of the high level. This strongly emphasizes that economic motives are the dominant motivation for women’s crime in Kurdish society. As for comparing the causes and motives of the crime according to some of the personality traits of women in Kurdish society who committed the crime, the results of the field study showed that there were no significant differences between the sample members according to variables (age, educational level, marital status, and monthly income). Where the statistical value (F) for the mentioned variables, the non-statistically significant value at the level of significance (0.05), and the differences between the arithmetic averages if any, did not reach the level of statistical significance, and therefore the research hypothesis is rejected and the zero hypothesis is accepted.